Aluminium-based metal matrix composites by stir casting: a literature review. (2016) - Kumar, Bharat; Menghani, Jyoti V.
This paper considers the potential of using Al metal matrix composite (MMC). Initially, the required properties are identified, after which, the work explores pure aluminium and its importance in the industry along with its limitations. Using these limitations, MMC's were recommended as a possible replacement for aluminium and it is seen that the exact set of properties depend on certain factors. Therefore, these factors such as reactivity at the interface, volume fraction of the reinforcing material, type of the reinforcing material and distribution of the reinforcing material are reviewed using the existing literature.